Surveillance of surgical site infection: more accurate definitions and more intensive recordings needed - Leaper, David; Tanner, Judith; Kiernan, Martin (Elsevier, 2013)
Surgical site infection (SSI) continues to be a burden on systems that deliver healthcare and on patients who suffer morbidity, and mortality, associated with this complication of medical intervention. Surveillance of SSI is often an integral part of organizational infection prevention and control activities, but unless post-discharge surveillance is carried out in a robust manner the data may be inaccurate and misleading. Coupled with a lack of robust application of definitions, variations in methods of case-finding and incomplete follow-up, the results may lead to a false sense of security or conversely cause unnecessary anxieties. Data from national surveillance schemes that purport to be suitable for benchmarking are often at odds with published rates from well-designed studies and the reasons for this should be examined. If benchmarking is truly desirable and if clinicians are to have confidence in the outputs, surveillance schemes should ensure that participating organizations adopt a consistent approach to definitions, case-finding methodologies following discharge, and to robust follow-up, to ensure that every opportunity is taken to maximize the return rate and enhance data validity.